Integration for development: Economic Complementation and Peruvian-Brazilian Border Cooperation - Díaz Palacios, Julio (1995)
The theme of the transoceanic highway is one of the most recurrent in the dialogue of those who are interested in the integration of Latin America, but particularly in the integration of Peru with Brazil, as an expression of a more creative and effective foreign policy. This is more evident in the southern Peruvian macro region, especially in the Andean jungle, Andean and coastal South. However, it is necessary to order and clarify ideas and proposals in order to help make the most convenient decisions for our two countries.